Search for excited muons in pp̄ collisions at s=1.96TeV - Abazov, V. M. (2006)
We present the results of a search for the production of an excited state of the muon, μ*, in proton antiproton collisions at s=1.96TeV. The data have been collected with the D0 experiment at the Fermilab Tevatron Collider and correspond to an integrated luminosity of approximately 380pb-1. We search for μ* in the process pp̄→μ*μ, with the μ* subsequently decaying to a muon plus photon. No excess above the standard model expectation is observed in data. Interpreting our data in the context of a model that describes μ* production by four-fermion contact interactions and μ* decay via electroweak processes, we set a 95% confidence level production cross section upper limit ranging from 0.057 to 0.112 pb, depending on the mass of the excited muon. Choosing the scale for contact interactions to be Λ=1TeV, excited muon masses below 618 GeV are excluded. © 2006 The American Physical Society.